A Cohort Study: Comorbidity and Stage Affected the Prognosis of Melanoma Patients in Taiwan - Chang, Chin-Kuo; Hsieh, Yih-Shou; Chen, Pei-Ni; Chu, Shu-Chen; Huang, Jing-Yang; Wang, Yu-Hsun; Wei, James Cheng-Chung (Frontiers in Oncology, 2022)
Background Comorbidities and stages may influence the prognosis of melanoma patients in Taiwan and need to be determined. Methods We performed a retrospective cohort study by using the national health insurance research database in Taiwan. Patients with a primary diagnosis of melanoma by the Taiwan Cancer Registry from 2009 to 2017 were recruited as the study population. The comparison group was never diagnosed with melanoma from 2000 to 2018. The Charlson comorbidity index was conducted to calculate the subjects’ disease severity. The Cox proportional hazards model analysis was used to estimate the hazard ratio of death. Results We selected 476 patients, 55.5% of whom had comorbidity. A higher prevalence of comorbidity was associated with a more advanced cancer stage. The mortality rate increased with an increasing level of comorbidity in both cohorts and was higher among melanoma patients. The interaction between melanoma and comorbidity resulted in an increased mortality rate. Conclusion An association between poorer survival and comorbidity was verified in this study. We found that the level of comorbidity was strongly associated with mortality. A higher risk of mortality was found in patients who had localized tumors, regional metastases, or distant metastases with more comorbidity scores. Advanced stage of melanoma patients with more comorbidities was significantly associated with the higher risk of mortality rate.